Museum Mpu Purwa Di Malang - andini, wulan (Maliki Interdisciplinary Journal, 2025)
The Mpu Purwa Museum in Malang City is an attractive and modern educational tourism destination, designed to provide comfort for visitors. With large, clean and bright architecture, this museum holds a collection of cultural heritage objects from the Hindu-Buddhist kingdom. Consisting of two buildings, namely the collection building and staff building and library, this museum provides adequate facilities to support learning activities. As a Center for the Rescue of Antiquities, the Mpu Purwa Museum displays various historical artifacts and statues that are silent witnesses of past civilizations. Visitors can enjoy an interactive and informative learning experience without entrance fees, making it accessible to all groups. The presence of security guards also ensures that visitors feel safe and comfortable when visiting. This museum is very important for students and the general public in exploring information about the history of the Indonesian nation. By visiting museums, we not only enrich our knowledge about cultural heritage, but also show a sense of nationalism and pride as citizens. Therefore, taking advantage of the facilities provided by the government to learn about the history and culture of the nation is a positive step in maintaining identity and fostering a sense of love for the country